Natural medicines of targeted rheumatoid arthritis and its action mechanism - Liu, Xueling; Wang, Zhiguo; Qian, Hua; Tao, Wenhua; Zhang, Ying; Hu, Chunyan; Mao, Weiwei; Guo, Qi (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease involving joints, with clinical manifestations of joint inflammation, bone damage and cartilage destruction, joint dysfunction and deformity, and extra-articular organ damage. As an important source of new drug molecules, natural products have many advantages, such as a wide range of biological effects and small toxic and side effects. They have become a hot spot for the vast number of researchers to study various diseases and develop therapeutic drugs. In recent years, the research of natural products in the treatment of RA has made remarkable achievements. These natural products mainly include flavonoids, polyphenols, alkaloids, glycosides and terpenes. Among them, resveratrol, icariin, epigallocatechin-3-gallate, ginsenoside, sinomenine, paeoniflorin, triptolide and paeoniflorin are star natural products for the treatment of rheumatoid arthritis. Its mechanism of treating RA mainly involves these aspects: anti-inflammation, anti-oxidation, immune regulation, pro-apoptosis, inhibition of angiogenesis, inhibition of osteoclastogenesis, inhibition of fibroblast-like synovial cell proliferation, migration and invasion. This review summarizes natural products with potential therapeutic effects on rheumatoid arthritis and briefly discusses their mechanisms of action against RA.